Flexor Tendons Contracture in a Weaned Caracu Calf - Farias Passos, Rebeca; Barbosa Aquino Silva, Igor Gabriel; Santos, Fernanda Carlini Cunha (Acta Scientiae Veterinariae, 2024)
Background: Limb pathologies can negatively influence productive and reproductive performance on cattle, as well as welfare and quality of life. Flexural deformities are common congenital alterations in newborn calves. Contracture of the forelimbs flexor tendons can be classified in mild, moderate, and severe. Mild and moderate cases can be treated with drugs and physiotherapy. Severe cases can become more challenging due to locomotion difficulties, being surgical correction recommended. Prognosis depends on the involvement degree and evolution period. The objective of the present report was to describe the case of congenital flexural deformity in the thoracic limbs in a weaned Caracu calf, with severe hyperflexion of the flexor tendons and weight bearing in the carpal region. Case: A 8-month-old Caracu breed calf, male, not castrated, was attended due to kneeling position. The calf presented the alteration since birth, but the owner only called for veterinarian assistance after weaning. On physical examination, the animal presented locomotion difficulty, with abnormal positioning of the thoracic limbs, severe bilateral hyperflexion and weight bearing in the carpal region. The left thoracic limb also presented lateralization. Forced manual extension of the limbs was difficult, with minimal movement. Given the anamnesis and physical examination, the definitive diagnosis was congenital flexural deformity, with contracture of the flexor tendons in the thoracic limbs. The calf possibly also had joint lesions in both carpals, due to constant weight support. The recommended treatment was surgical, with the owner being instructed about the main complications, in addition to possible non-responsiveness to treatment due to long evolution period. Surgical correction was performed using the superficial and deep digital flexor tenotomy technique in both thoracic limbs. Immediately after surgery, the calf presented slight relaxation of the thoracic limbs, however, even after weeks, no progressive improvement was observed. Approximately 22 months after surgery, the animal reached the required weight and was sent for slaughter. Discussion: Treatment for flexor tendon contracture varies depending on the severity of the limb alteration, including clinical and surgical therapy. Time elapsed between the appearance of the alteration and the institution of treatment is a very relevant factor, influencing the prognosis. Greater chances of success and a better prognosis are observed when flexural deformities are diagnosed and treated as early as possible. In the present report, time elapsed between the appearance of the change (at birth) and the professional assessment (8 months) was a decisive factor regarding failure of surgery and the patient’s evolution. Due difficulty in moving around to feed, injuries to other joints in the limbs, presence of wounds in the support region, most cases end with slaughtering. The weaned Caracu calf presented congenital flexural deformity, with severe hyperflexion of the flexor tendons and weight bearing in the carpus region, with surgical treatment performed by tenotomy of the digital flexors. However, the treatment did not achieve the expected results, probably due to the presence of chronic alterations in other joints, making it difficult to extend the limbs, in addition to the animal’s age and the delay between diagnosing the disorder and instituting appropriate treatment. Considering the use of the animal, which was meat production, treatment allowed an improvement in the quality of life and provided the opportunity for greater weight gain, until the moment of destination for slaughter. Keywords: bovine, congenital defects, flexural deformity, lameness, tenotomy. Título: Contratura dos tendões flexores em bezerro Caracu desmamado Descritores: bovinos, defeitos congênitos, deformidade flexural, claudicação, tenotomia.